Probabilistic Cost Optimization of Green Retrofitting in Transit-Oriented Development Using Monte Carlo Simulation and CASBEE Criteria - Reza Dwi Rukmono; Mawardi Amin; Budi Susetyo (Postgraduate, University of Mataram, 2026)
Bekasi City faces serious environmental issues due to climate change, rapid urbanization, and high urban activity, which have resulted in increased carbon emissions, air pollution, and declining environmental quality. The application of green building and green infrastructure concepts, including the utilization of building rooftops, renewable energy, and air management, is an effective solution to improve energy efficiency and urban environmental quality. This study aims to improve the cost efficiency of green retrofitting in Transit Oriented Development (TOD) by utilizing CASBEE (Comprehensive Assessment System for Built Environment Efficiency) guidelines and Montecarlo @Oracle Crystal Ball probabilistic simulation technology. This study was conducted at the Eastern Green TOD in Bekasi, where the cost of implementing green building concepts in urban environments is increasingly becoming a major concern. With this approach, the study throws up various factors that influence cost performance and implements Montecarlo @Oracle Crystal Ball probabilistic simulation methods to obtain more accurate predictions regarding costs and efficiency. This study has the potential to become a reference for developers in implementing green building principles in TOD areas, as well as supporting better decision-making regarding costs and project sustainability.